2008
DOI: 10.1111/j.1469-8137.2008.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological adjustment of two Sphagnum species in response to anthropogenic nitrogen deposition

Abstract: Summary• Here, it was investigated whether Sphagnum species have adjusted their nitrogen (N) uptake in response to the anthropogenic N deposition that has drastically altered N-limited ecosystems, including peatlands, worldwide.• A lawn species, Sphagnum balticum, and a hummock species, Sphagnum fuscum, were collected from three peatlands along a gradient of N deposition (2, 8 and 12 kg N ha). The mosses were subjected to solutions containing a mixture of four N forms. In each solution one of these N forms was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 75 publications
2
56
1
2
Order By: Relevance
“…In line with this, several authors have found indications that mosses from high N deposition sites cope better with N addition than mosses from low N deposition sites (Baxter et al 1992;Limpens and Berendse 2003;Press et al 1986). Local adaptation to regional N deposition has also recently been suggested in mosses and vascular plants (Vergeer et al 2008, Wiedermann et al 2008. However, in our study we cannot separate an adaptive response to N deposition from a physiological adjustment (e.g.…”
Section: Ecological Consequencesmentioning
confidence: 78%
“…In line with this, several authors have found indications that mosses from high N deposition sites cope better with N addition than mosses from low N deposition sites (Baxter et al 1992;Limpens and Berendse 2003;Press et al 1986). Local adaptation to regional N deposition has also recently been suggested in mosses and vascular plants (Vergeer et al 2008, Wiedermann et al 2008. However, in our study we cannot separate an adaptive response to N deposition from a physiological adjustment (e.g.…”
Section: Ecological Consequencesmentioning
confidence: 78%
“…NH4 + is preferentially taken up by Sphagnum (Fritz et al, 2014;Liu et al, 330 2013; Wiedermann et al, 2009) because Sphagnum has a high cation exchange capacity 331 (Bates, 1992;Gunnarsson & Rydin, 2000). In addition, NH4 + has greater toxicity 332 (Gerendás et al, 1997;Krupa, 2003;Stevens et al, 2011).…”
Section: Science Of the Total Environment Chiwa Et Al Revised Msmentioning
confidence: 99%
“…(NH4 + ) versus oxidized (NO3 -) N on the N status of the Sphagnum moss and the (Manninen et al, 2011;Sheppard et al, 2014), possibly due to the greater toxicity of 97 NH4 + (Gerendás et al, 1997;Krupa, 2003;Stevens et al, 2011;Limpens and Berendse, 98 2003) coupled to preferential uptake of NH4 + by Sphagnum (Fritz et al, 2014;Liu et al, 99 2013; Wiedermann et al, 2009). For example, Manninen et al (2011) found that NH4 + 100 addition increased shoot N concentration of Sphagnum and decreased photosynthetic 101 variables (Fv/Fm) and shoot dry weight of Sphagnum.…”
mentioning
confidence: 99%
“…Similarly, specimens originating from high N deposition areas take up less N than those originating from low N deposition regions [51]. Therefore, decreased N uptake may be a long-term adaptation for bryophytes subjected to high N supply [51, 52]. Several authors have suggested that specimens subjected to long-term N enrichment display a plastic response to new environmental scenarios through higher tissue N concentration [53], or reduced N uptake [52] or physiological acclimation [51].…”
Section: Discussionmentioning
confidence: 99%